How do cancer cells cope with supernumerary centrosomes? - Dores, Katharina Santos das (2015)
Cancer kills one in five people each year in western societies, therefore clinicians are eager to find novel diagnostic, prognostic and therapeutic tools to predict outcomes and treat patients. More than a century ago, Theodor Boveri suggested that numerical abnormalities in the centrosome, the major Microtubule Organizing Centre (MTOC) in animal cells, cause abnormal cell division and tumour formation. Extra centrosomes promote aberrant cell divisions, which can induce the formation of more than two non-viable daughter cells. However cancer cells often divide successfully and survive by clustering (i.e. gathering) their supernumerary centrosomes. Our previous work has indeed shown that centrosome defects are widespread in the NCI-60 panel of cancer cell lines and that centrosome clustering is the main but not the sole coping mechanism with centrosome amplification. With this thesis, I wanted to investigate a) how widespread clustering is in the NCI-60 panel, b) what alternative coping mechanisms exist and how widespread they are, and c) how cells divide in presence of alternative mechanisms. To answer these questions, we screened the centrosome clustering ability of 27 cancer cell lines using immunofluorescence images of mitotic cells displaying centrosome amplification. This work showed that centrosome clustering is widespread in cancer and highlighted the presence of alternative mechanisms, i.e. centrosome extrusion and inactivation, for the first time in cancer. Furthermore, I observed that most of the cell lines divide in a bipolar fashion by combining the different coping mechanisms. Further studies are now required to highlight the cellular and molecular machineries regulating the alternative mechanisms as they represent exploitable Achilles’ heels of cancer cells for the development of innovative drugs to selectively kill cancer.